2019
DOI: 10.1177/2055102919838909
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s nice to just be you’: The influence of the employment experiences of UK military spouses during accompanied postings on well-being

Abstract: Repeated military relocations (accompanied postings) can have a detrimental effect on employment and well-being among the spouses and partners of military personnel. Semi-structured telephone interviews were conducted with 19 spouses of British Army/Royal Air Force personnel with recent experience of accompanied postings to explore this issue through the lens of self-determination theory; all were married women with at least one child. Participants explained how employment contributed to an independent identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…In addition to the happiness for the return of the soldier home, these results may also be linked to the benefits and potentialities associated with the mission, such as a change at the personal level (independence, self-efficiency, maturity) and at the interpersonal relationship level, that is, reinforcement of family bonds, in particular with the spouse. These facts were also identified in previous studies on service members spouses (Barbudo et al, 2014; Bóia et al, 2018; Gribble et al, 2019) as positively influencing well-being (Gribble et al, 2019). Additionally, the clarification and/or strengthening of marital relationships may be a positive achievement (Barbudo et al, 2014; Karney & Crown, 2007).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition to the happiness for the return of the soldier home, these results may also be linked to the benefits and potentialities associated with the mission, such as a change at the personal level (independence, self-efficiency, maturity) and at the interpersonal relationship level, that is, reinforcement of family bonds, in particular with the spouse. These facts were also identified in previous studies on service members spouses (Barbudo et al, 2014; Bóia et al, 2018; Gribble et al, 2019) as positively influencing well-being (Gribble et al, 2019). Additionally, the clarification and/or strengthening of marital relationships may be a positive achievement (Barbudo et al, 2014; Karney & Crown, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…Soldiers’ spouses also showed significant changes in several variables during the three phases of the mission, which, as Gribble, Goodwin, Oram, and Fear (2019) stated, could have influenced their well-being. Actually, in predeployment and deployment waves, they evidenced greater anxiety and family difficulties when compared with postdeployment, which is in accordance with theoretical models (Logan, 1987; Peebles-Kleiger & Peebles-Kleiger, 1994; Pincus et al, 2001) and empirical studies about military families (Barbudo et al, 2014; Johnson et al, 2007; Nichols & Martindale-Adams, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…Participants identified that dependency on their (ex)partner impaired their ability to seek help and perpetuated the cycle of IPVA. Financial dependency and isolation may be a particular barrier for the civilian partners of military personnel, as frequent military-related relocations have been found to disrupt spouses’ social networks and ability to maintain employment (Blakely et al, 2014 ; Gribble et al, 2019 ) and the military may provide housing and other welfare support (Sparrow et al, 2020 ), which they would lose if the relationship ended. Adding further weight to previous study findings of help-seeking for IPVA in the military community, these barriers were especially heightened for FCO participants, whose circumstances, such as a reliance on their (ex)partner both financially and for the right to remain in the country, as well as their isolation from their own communities, impaired their ability to seek help (Gray, 2016 ; Sparrow et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…UK research indicates the challenges that military spouses face when looking for employment as part of a mobile population [ 3 ], suggesting that these challenges can impact negatively on the psychological well-being of military spouses [ 42 ]. This is consistent with US and Canadian literature, where career and employment opportunities of military spouses have been shown to be negatively influenced by frequent and repeated military relocations [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%